Four vertex technique for correcting urethral prolapse: technique description and cohort study - Noya-Mourullo, Andrea; Herrero-Polo, Manuel; Heredero-Zorzo, Oscar; García-Gómez, Francisco; Urrea-Serna, Carmen; Marquez-Sanchez, Magaly-Teresa; Flores-Fraile, Javier; Padilla-Fernandez, Barbara-Yolanda; Lorenzo-Gómez, María-Fernanda (Frontiers in Surgery, 2023)
Introduction/Objectives: Urethral prolapse predominantly affects postmenopausal women and prepubertal girls. Here we describe the procedure and effectiveness of surgical correction of urethral prolapse with the “four vertex” technique, and identify the variables which influence postoperative outcomes. Methods and Materials: Surgical technique is described with high-quality imaging. Retrospective observational study of 17 adult women who underwent surgery for urethral prolapse at a tertiary referral hospital. Variables: Age, body mass index (BMI), medical and surgical history, concomitant diseases and treatments, state of health according to the ASA anaesthetic risk scale, vulnerability measured on the VES-13 scale, reason for consultation, time elapsed between diagnosis and surgery, results of the anatomical pathology report, functional outcomes, urinary incontinence before or after correction of prolapse, impact on sexual health. Two groups were defined based on the presence of a sensation of vaginal heaviness. Results: All patients were postmenopausal, with a mean age at the time of the intervention of 70.41 years, with no differences between groups. Mean BMI was 23.67 kg/m2, higher in the group with a sensation of vaginal heaviness (p=0.027). Mean time elapsed between diagnosis and operation was 231.58 days, with no differences between groups. Mean childbirth count was 2.29. The most frequent causes for consultation were urethrorrhagia (33.33%) and a bulging sensation (33.33%). After the intervention, 14 patients (82.35%) were asymptomatic, two (11.76%) had dysuria, and one (5.88%) had urinary urgency. Ten patients had pre-surgical urinary incontinence, which was resolved in nine patients. 17.46% subsequently presented pelvic organ prolapse. In three women there was secondary impairment of sexual activity. Conclusion: The four vertex surgical technique for the correction of urethral prolapse results in complete clinical remission in 82.35% of women. Conditions which worsen postoperative outcomes are concomitant cystocele, presence of urinary incontinence, and delay in treatment.